Exact solution of an anisotropic J1–J2 model with the Dzyloshinsky–Moriya interactions at boundaries. (13th May 2021) - Cao, Yusong; Wang, Jian; Qiao, Yi; Cao, Junpeng; Yang, Wen-Li
Abstract: We propose a method to construct new quantum integrable models. As an example, we construct an integrable anisotropic quantum spin chain which includes the nearest-neighbor, next-nearest-neighbor and chiral three-spin couplings. It is shown that the boundary fields can enhance the anisotropy of the first and last bonds, and can induce the Dzyloshinsky–Moriya interactions along the z -direction at the boundaries. By using the algebraic Bethe ansatz, we obtain the exact solution of the system. The energy spectrum of the system and the associated Bethe ansatz equations are given explicitly. The method provided in this paper is universal and can be applied to constructing other exactly solvable models with certain interesting interactions.